Vanin 1 gene role in modulation of iNOS/MCP-1/TGF-β1 signaling pathway in obese diabetic patients - Mosaad, Yasser O.; Hussein, Mohammed Abdalla; Ateyya, Hayam; Mohamed, Ahmed H.; Ali, Ali A.; Youssuf, Alaa Ramadan; Wink, Michael; El-Kholy, Amal A. (Journal of inflammation research, 2022)
changes in Vanin-1 gene expression in obese, diabetic patients may be related to changes in glycemic, inflammatory, and redox factors.
Gesehen am 21.06.2023